Grief of Parents Over The Death of A Child: Homicide Case Studies in Manokwari, West Papua - Ni Luh Ayu Megawati Putri; Aloysius L.S. Soesilo (UNS Press, 2021)
Loss due to violent and unexpected death results in a deep grief for the parents of the victim. Their struggle to make sense and to cope with this terrible event such as this has been the focus of this case study, which was based on the real case of homicide of a female university student in Manokwari in October 2016. This case and its court proceedings had attracted a great deal of attention among the local people of Manokwari. This qualitative case study involved two participants, the father and mother of the victim who had lived separately before the tragic event happened. Findings of the study demonstrates that both participants have undergone a prolonged grief, coupled with psychological trauma which has impacted their efforts to make adjustment to their daily lives after the loss. Implications of this study for further studies and practical aspects for psychosocial services for people with similar conditions are also discussed.